Mandibular range of motion in children with juvenile idiopathic arthritis with and without clinically established temporomandibular joint involvement and in healthy children; a cross-sectional study - Willemijn F. C. de Sonnaville; Caroline M. Speksnijder; Nicolaas P. A. Zuithoff; Daan R. C. Verkouteren; Nico W. Wulffraat; Michel H. Steenks; Antoine J. W. P. Rosenberg (BMC, 2021)
Abstract Background Recognition of temporomandibular joint (TMJ) involvement in children with juvenile idiopathic arthritis (JIA) has gained increasing attention in the past decade. The clinical assessment of mandibular range of motion characteristics is part of the recommended variables to detect TMJ involvement in children with JIA. The aim of this study was to explore explanatory variables for mandibular range of motion outcomes in children with JIA, with and without clinically established TMJ involvement, and in healthy children. Methods This cross-sectional study included children with JIA and healthy children of age 6-18 years. Mandibular range of motion variables included active and passive maximum interincisal opening (AMIO and PMIO), protrusion, laterotrusion, dental midline shift in AMIO and in protrusion. Additionally, the TMJ screening protocol and palpation pain were assessed. Adjusted linear regression analyses of AMIO, PMIO, protrusion, and laterotrusion were performed to evaluate the explanatory factors. Two adjusted models were constructed: model 1 to compare children with JIA and healthy children, and model 2 to compare children with JIA with and without TMJ involvement. Results A total of 298 children with JIA and 169 healthy children were included. Length was an explanatory variable for the mandibular range of motion excursions. Each centimeter increase in length increased AMIO (0.14 mm), PMIO (0.14 mm), and protrusion (0.02 mm). Male gender increased AMIO by 1.35 mm. Having JIA negatively influenced AMIO (3.57 mm), PMIO (3.71 mm), and protrusion (1.03 mm) compared with healthy children, while the discrepancy between left and right laterotrusion raised 0.68 mm. Children with JIA and TMJ involvement had a 8.27 mm lower AMIO, 7.68 mm lower PMIO and 0.96 mm higher discrepancy in left and right laterotrusion compared to healthy children. Conclusion All mandibular range of motion items were restricted in children with JIA compared with healthy children. In children with JIA and TMJ involvement, AMIO, PMIO and the discrepancy between left and right laterotrusion were impaired more severely. The limitation in protrusion and laterotrusion was hardly clinically relevant. Overall, AMIO is the mandibular range of motion variable with the highest restriction (in millimeters) in children with JIA and clinically established TMJ involvement compared to healthy children.